Penerapan Konseling Behavioristik dengan Teknik Self Management untuk Mereduksi Perilaku Adiksi Sosial Pengguna Gadget pada Peserta Didik - Rida Hartika Sari; Budiyanto Budiyanto; Najlatun Naqiyah (MODELING: Jurnal Program Studi PGMI, 2021)
This study aims to determine the significance of the decrease in addictive behavior of gadget users in class XI students at SMA Negeri Surabaya through a behavioristic counseling approach with self-management techniques. This type of research uses a quasi-experimental methodology with a one group pre-test post-test design model with the aim of helping researchers to run effectively for experiencing constraints such as the COVID-19 pandemic. The process of taking the subject with purposive sampling, namely 10 students in class XI. Analysis of data results by testing the Wilcoxon ranks test and descriptive analysis. The results of the study proved that the behavioristic group counseling services with self-management techniques were able to significantly reduce the addictive behavior of gadget users in students.